A case study analysis of person-centred-planning for people with intellectual disability following their transfer from institutional care - Fitzsimons, Donal (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2012)
Person centred planning (PCP) has an essential part to play in ensuring self determination for the lives of people with intellectual disability. It is typically taken as an indicator to the quality of services and it is regarded as especially important when considering its effectiveness in impacting on the lives of people with intellectual disability. Robertson’s et al (2005) six indices of PCP efficacy of social networks, community involvement, scheduled day services, contact with friends, contact with family and choice are regarded as a standard measure. This research examined the PCP process and its impact on the reality of the life of the person with intellectual disability. It considered the understanding of various stakeholders in the PCP process and investigated whether PCP brings added value to the lives of people with intellectual disability in community settings. Finally, it explored the relationship between the theory, policy, and outcomes of PCP for ongoing practice.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin